Diagnosis and management of coronary artery disease in early surgical treatment of acute infective endocarditis of the aortic valve. (25th November 2020) - Knol, W.G; Wahadat, A.W; Roos-Hesselink, J.W; Tanis, W; Hirsch, A; Van Mieghem, N.M; Bogers, A.J.J.C; Budde, R.P.J
Abstract: Background: The need to routinely screen for coronary artery disease (CAD) in asymptomatic patients undergoing surgery for acute aortic valve infective endocarditis (IE) is debated. There is concern about the risk of embolization during invasive coronary angiography (ICA), especially in patients with vegetations. Coronary computed tomography angiography (cCTA) is a non-invasive alternative. Purpose: To evaluate the prevalence of CAD in patients with acute aortic valve IE, the safety and feasibility of ICA and cCTA for diagnosis of CAD, and CAD related postoperative outcomes. Methods: In this single center retrospective cohort study, all patients with acute infective aortic valve endocarditis between 2009–2019 undergoing surgery were selected. Outcomes were embolization after preoperative ICA, in-hospital mortality, perioperative myocardial infarction or unplanned revascularization. Results: 159 patients (mean age 58±15, 81% male) underwent surgery. No CAD screening was done in 46/145, a cCTA was performed in 54/145 patients and an ICA in 52/145 patients. In 1 of the 52 patients undergoing preoperative ICA a cerebral embolism occurred. cCTA was not assessable on a patient level in 2 patients and 7 patients underwent both cCTA and ICA. Significant CAD was found in about 20% of patients both after cCTA and ICA. Even though just a minority of patients with CAD was treated with concomitant CABG, only 1 patient with known but untreated CAD needed unplanned revascularization postoperatively. The rate of perioperative myocardial infarction or unplanned revascularization in patients not screened for CAD was 5% (3 patients). Conclusion: In patients with acute aortic valve IE the prevalence of CAD is low (14%). The risk of embolism after preoperative ICA is not negligible and should be carefully weighed against the estimated risk of CAD-related perioperative complications. cCTA might serve as a gatekeeper for ICA in many patients with acute aortic IE. Funding Acknowledgement: Type of funding source: None